Impacts of Digital Financial Inclusion on Urban-rural Income Gap in China - Jing, Liu (UNIMAS, 2024)
In order to solve the existing technical limitations, asymmetry in information issues between lenders and borrowers, imperfect supervision and management policies, network security and other matters on the evolution of digital financial inclusion in country areas of China are hindered. In the meantime, the matter of excessive earning disparity between urban-rural inhabitants in China should be further alleviated, so as to alleviate the occurrence of financial exclusion in China. This study explores the impact of digital financial inclusion on the urban-rural earning disparity in China from different dimensions of digital financial inclusion. This study empirically investigates the impact of digital financial inclusion on urban-rural income disparity in China by collecting a substantial amount of provincial-level data, including the digital financial inclusion index, urban and rural income levels, and other relevant indicators. The study focuses on the overall index of digital financial inclusion (primary dimension), which includes depth, coverage, and digitization (secondary dimensions), as well as digitalization-specific indices such as the payment index, insurance index, and credit index (tertiary dimensions), amounting to a total of seven indicators. Furthermore, the study conducts a comparative analysis of the influence of digital inclusive finance on urban-rural income disparity in China’s eastern and western regions. Quantitative analysis methods are employed, and Stata software is used for empirical analysis. Pooled Ordinary Least Squares (POLS), Fixed Effects Models (FE), and Random Effects (RE) Models are applied to the compiled data. The empirical findings of the study indicate that, the digital financial inclusion can reduce the income disparity between urban and rural areas in China. The evolution of the total index of digital financial inclusion can effectively converge the income disparity between urban and rural areas in China. The breadth of coverage and the depth of use have an important influence on narrowing the income disparity. The influence of digitalization degree on income disparity is also negative, but not significant. The insurance index has a significant effect on income inequality. The effect of payment index and credit index on income disparity is not significant. Simultaneously, the development of digital financial inclusion in the eastern economic zone and western economic zone can converge the income disparity, respectively. The convergence effect of digital financial inclusion on the income disparity in the western zone of China is better than that in the eastern region. The credit index converges the income disparity in western China less than that in eastern China. In the other six indicators of digital financial inclusion, the convergence effect in the western is better than that in the eastern. Digital financial inclusion not only converge the income disparity in the eastern and western zones, but also accelerate the economic growth of the western, so as to converge the disparity between the western and eastern zones. In light of these research findings, this thesis proposes effective recommendations to promote the development of digital financial inclusion in China, further narrowing the income disparity between urban and rural residents and addressing the development disparity between the eastern and western regions.